A narrative review of the physiology and health effects of burnout associated with veterinarian-pertinent occupational stressors - Steffey, Michele A.; Griffon, Dominique J.; Risselada, Marije; Buote, Nicole J.; Scharf, Valery F.; Zamprogno, Helia; Winter, Alexandra L. (Frontiers in Veterinary Science, 2023)
Chronic workplace stress and burnout are serious problems in veterinary medicine. Although not classified as a medical condition, burnout can affect sleep patterns and contributes to chronic low grade systemic inflammation, autonomic imbalance, hormonal imbalances and immunodeficiencies, thereby increasing the risks of physical and psychological ill health in affected individuals. Cultural misconceptions in the profession often lead to perceptions of burnout as a personal failure, ideas that healthcare professionals are somehow at lower risk for suffering, and beliefs that affected individuals can or should somehow heal themselves. However, these concepts are antiquated, harmful and incorrect, preventing the design of appropriate solutions for this serious and growing challenge to the veterinary profession. Veterinarians must first correctly identify the nature of the problem and understand its causes and impacts before rational solutions can be implemented. In this first part of two companion reviews, burnout will be defined, pathophysiology discussed, and healthcare and veterinary-relevant occupational stressors that lead to burnout identified.